A discrete-choice experiment study of physicians' prioritization of attributes of medical treatments for endometriosis-associated pain. (2nd January 2023) - Poulos, Christine; Xu, Yanqing; Botha, Willings; Leach, Colton; Wrobleski, Kristin Kahle; Gordon, Keith; Missmer, Stacey A.; Estes, Stephanie J.
ABSTRACT: Background: Physicians' preferences for attributes of medical treatments for endometriosis-associated pain have not previously been quantified. Methods: US obstetrician-gynecologists completed an online discrete-choice experiment survey. In a series of questions, physicians chose a medical treatment for a hypothetical patient with endometriosis experiencing severe, persistent dysmenorrhea, nonmenstrual pelvic pain, and/or dyspareunia. Each question presented two hypothetical medical treatments for endometriosis-associated pain, defined by seven attributes with varying levels. Preferences weights and conditional relative importance (CRI) were calculated using a random-parameters logit model. Results: Respondents (N = 250) had an average age of 53 years; 36% were female. The most important attribute, conditional on the attributes and levels evaluated, was risk of moderate-to-severe hot flashes (CRI, 3.34). In descending order of importance, the CRIs of the other attributes were 2.13 for improvement in nonmenstrual pelvic pain, 2.04 for improvement in dyspareunia, 1.88 for improvement in dysmenorrhea, 1.16 for risk of pregnancy-related complications if pregnancy occurs during treatment, 0.62 for increased risk of bone fracture later in life, and 0.48 for mode of administration. Conclusions: In addition to valuing pain reduction, respondents prioritized avoiding moderate-to-severe hot flashes, followed by less common and less immediate risks of pregnancy-related complications and bone fracture.